Accidents in railway transportation: Lessons learned from Thailand and France - Sripathomswat Kanokporn; Promkamol Lattapon; Romruen Worachon; Arthaud Quentin; Drouin Alban (E3S Web of Conferences)
Thailand’s railway network spans over 4,000 kilometres, comprising five lines that extend across all regions of the country. This research focuses on applying hazard management techniques, particularly in establishing accident frequency and severity indices to evaluate accident data at railway crossings in Thailand. Utilizing accident data from the Department of Rail Transport’s open database (2017-2022), the study aims to identify the most dangerous railway locations in Thailand. To enhance the analysis, geographic information system (GIS) methodologies are employed to visualize accessibility data and identify disparities across different train lines. In a complementary part of the study, French railway incident data are analysed. Security incidents, sourced from the open data of SNCF France and provided by the Établissement Public de Sécurité Ferroviaire (EPSF), are visualized. The research highlights differences in incident severity between the two countries. By comparing these two contexts, the study offers insights into how to restore public confidence in the railway transportation system, emphasizing the importance of tailored hazard management approaches.